Childhood lymphoma in Yorkshire. Issue 2 (February 1992) - Davison, A M; McKinney, P A; Bailey, C C; Lewis, I; Cartwright, R A; O'Brien, C
Abstract : AIMS: A histopathological review of 43 cases of childhood non-Hodgkin's lymphoma (NHL) in an attempt to identify histological variables of prognostic importance. METHOD: Each case was reclassified according to the Working Formulation and an attempt made to allocate an immunophenotype using a panel of monoclonal antibodies. Results were correlated with clinical data on site and survival. RESULTS: Of the 43 cases, 30 were males and 13 females. There were 17 cases of lymphoblastic lymphoma, 15 cases of small non-cleaved cell lymphoma (SNCC), and four cases of large cell lymphoma. The SNCC group was subdivided into 10 cases of Burkitt's lymphoma and five cases of non-Burkitt's lymphoma. An immunophenotype was allocated in 65.1% of cases (23 B, 5 T). The SNCC cases were spread throughout the 0-16 year age range while the lymphoblastic lymphoma cases tended to occur in older children. Most mediastinal tumours were lymphoblastic lymphoma and most abdominal tumours were SNCC. Statistical analysis failed to show a significant difference in survival among histological subgroups or immunophenotypes. CONCLUSION: No histological variables of prognostic importance were identified partly due to the great variation in treatment regimens, standard of supportive care, and prognosis over the period of the study (1972 to 1988).